Medicinal plants used Against Typhoid Fever and Toothache in Pir-Panchal Range of the Shopian District of Kashmir Himalaya. - Singh, Sumer; Khanday, Zakir Hussain (Journal of Phytology, 2017)
Â  The present study was undertaken with a view to explore the possibilities of utilizing the plant resources of the district Shopian. A total of plant / specimens along with detailed information and their uses would serve as a valuable record for future reference & study. Most of these plants are wild and some plants are cultivated. The present study reveals that 22 medicinal plants belonging to 14-families are being used for Typhoid fever & Toothache in the Shopian district of Kashmir Himalaya. Of these 22 medicinal plants, 5 plant species are used both for fever and toothache. These medicinal plants have been arranged alphabetically. Despite extensive use of medicinal plants by the people of this region, extensive work has not been done as yet on ethnomedicinal& other aspects. The present study is an attempt to generate interest among the society regarding the potential of natural alternatives in preventing Typhoid fever and Tooth diseases in the study area.Â 